Slow-release of fluorite and its effect on flotation separation of magnesite from calcite. (July 2022) - Wang, Ruolin; Han, Haisheng; Sun, Wenjuan; Sun, Wei; Wei, Zhao; Chen, Wensheng; Wang, Jian
Highlights: Fluorite particles slowly release fluoride ions (F - ) to chemisorb on calcite surface. The amount slow-released F - is small but this released process is continuous. The inhibiting effect of fluorite is better than that of sodium fluoride. Fluorite particles can achieve the flotation separation of magnesite from calcite. CaF2 films are easily generated on calcite surface to decrease the floatability. Abstract: The flotation separation of magnesite from calcite under Pb-BHA collector system is difficult due to the same action site of CO3 2– anion. Surface transformation of fluorite particles present great selectivity for different calcium containing minerals, which is due to the selective adsorption of slowly-released fluoride ions (F - ). The application of surface transformation and Pb-BHA collectors can achieve the efficient separation of magnesite and calcite. This study suggests that the floatability of magnesite is similar to that of calcite without any depressant, and the presence of fluorite triggers a selectively inhibiting action on calcite but not on magnesite. Zeta potential and X-ray photoelectron spectroscopy measurements indicate that slowly-released F - from fluorite particles strongly is chemisorbed on the surface of calcite instead of magnesite, and the adsorbed F - react with Ca 2+ on the calcite surface to generate CaF2 . Atomic force microscopy measurement confirms that a CaF2 films is formed to change the surface morphology of calcite and increase the surface roughness. Furthermore, the slow release of fluorite particles can precisely control the adsorption and the surface transformation of F- on calcite, instead on magnesite. Therefore, the slow release and surface transformation of fluorite particles plays an important role in the flotation separation of carbonate minerals.